2013
DOI: 10.1007/s10773-013-1585-4
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Charged Thin-Shell Wormholes in (2+1) Dimensions

Abstract: In this paper we construct charged thin-shell wormholes in (2+1)-dimensions applying the cut-andpaste technique implemented by Visser, from a BTZ black hole which was discovered by Bañados, Teitelboim and Zanelli [1], and the surface stress are determined using the Darmois-Israel formalism at the wormhole throat. We analyzed the stability of the shell considering phantom-energy or generalised Chaplygin gas equation of state for the exotic matter at the throat. We also discussed the linearized stability of char… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…This method was applied to construct a number of thinshell wormholes (TSW), including charged TSW [11,12], TSW with a cosmological constant [13], TSW in dilaton gravity [14], TSW from the regular Hayward black hole [15], TSW in higher-dimensional Einstein-Maxwell theory [16,17], rotating TSW [18,19], quantum corrected TSW in Bohmian quantum mechanics [20], primordial wormholes induced from Grand Unified Theories (GUTs) [21,22], canonical acoustic TSW, charged TSW with dilaton field, TSW with a Chaplygin gas, traversable wormholes in the anti-de Sitter space-time, TSW with a negative cosmological 2 Advances in High Energy Physics constant, wormholes in mimetic gravity, TSW from charged black string, cylindrical TSW, and many other interesting papers , while the stability analysis is investigated by different models, for example, linear perturbations [9] and specific equations of state (EoS) such as linear barotropic gas (LBG), Chaplygin gas (CG), and logarithmic gas (LogG) for the exotic matter [14,[59][60][61][62].…”
Section: Introductionmentioning
confidence: 99%
“…This method was applied to construct a number of thinshell wormholes (TSW), including charged TSW [11,12], TSW with a cosmological constant [13], TSW in dilaton gravity [14], TSW from the regular Hayward black hole [15], TSW in higher-dimensional Einstein-Maxwell theory [16,17], rotating TSW [18,19], quantum corrected TSW in Bohmian quantum mechanics [20], primordial wormholes induced from Grand Unified Theories (GUTs) [21,22], canonical acoustic TSW, charged TSW with dilaton field, TSW with a Chaplygin gas, traversable wormholes in the anti-de Sitter space-time, TSW with a negative cosmological 2 Advances in High Energy Physics constant, wormholes in mimetic gravity, TSW from charged black string, cylindrical TSW, and many other interesting papers , while the stability analysis is investigated by different models, for example, linear perturbations [9] and specific equations of state (EoS) such as linear barotropic gas (LBG), Chaplygin gas (CG), and logarithmic gas (LogG) for the exotic matter [14,[59][60][61][62].…”
Section: Introductionmentioning
confidence: 99%
“…Different TSW solutions have been proposed, including, charged TSW [8,9], TSW in heterotic string theory [10], TSW from a noncommutative BTZ black hole [11], TSW in Einstein-Maxwell-Gauss-Bonnet gravity [12], rotating TSW [13,14], TSW from scalar hair black hole [15], TSW supported by normal matter [16,17], cylindrical TSW [18][19][20][21][22][23][24], and TSW with a cosmological constant [25,26], and wormholes in the framework of mimetic gravity; see [27] and the references therein. Recently, Das [28], showed that by replacing the classical trajectories (geodesics) with the so-called quantal or Bohmian trajectories gives rise to the quantum version of the Raychaudhuri equation (QRE).…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by this work we provide thin-shell wormholes from noncommutative BTZ black hole in (2+1)-dimensional gravity. A well studied of thin-shell wormholes in lower dimensional gravity have been found in [67][68][69][70][71].…”
Section: Introductionmentioning
confidence: 99%